Factors affecting the price of housing in Malaysia - Ong, Tze San (Globalbiz Research, 2013)
The main purpose of this study is to measure the relationship between macroeconomic variables and the housing price. This paper examines empirically whether the increasing trend in the Malaysian housing price is related to changes in the gross domestic product (GDP), population, inflations rate, costs of construction, interest rate and real property gains tax (RPGT). The paper is exploratory in nature. The empirical data were collected from Valuation and Property Services Department of the Ministry of Finance Malaysia from 2001 to 2010. The paper provides empirical results that the gross domestic product (GDP), population and RPGT are the key determinants of housing prices. However, changes in housing prices may not necessarily be influenced by the gross domestic products (GDP), population and RPGT in Malaysia. The general finding of this paper strongly suggests that housing bubbles in the Malaysian residential property market are becoming bigger and stronger. The paper is useful for speculators, investors and buyers to know which factors to account for in housing investment decision. This paper can serve as a guide for the government in stabilizing the residential housing price in Malaysia.